The Relationship between Simple Snoring and Metabolic Syndrome: A Cross-Sectional Study - Juanjuan Zou; Fan Song; Huajun Xu; Yiqun Fu; Yunyan Xia; Yingjun Qian; Jianyin Zou; Suru Liu; Fang Fang; Lili Meng; Hongliang Yi; Jian Guan; et al. (Journal of Diabetes Research)
Purpose. This cross-sectional study was performed to assess the relationship between simple snoring and metabolic syndrome (MetS). Methods. A total of 5635 participants including 300 healthy volunteers without snoring allegedly were initially included from 2007 to 2016. Polysomnographic variables, anthropometric measurements, and biochemical indicators were collected. The polynomial linear trend test was used to assess the linear trend across snoring intensity for metabolic score, and logistic regression was used to evaluate the odds ratios (ORs) for MetS after controlling for age, sex, obesity, smoking status, and alcohol consumption. Results. The final study population consisted of 866 participants. Simple snorers showed more severe metabolic disorders and higher prevalence of MetS than nonsnorers. A significant linear trend was observed between snoring intensity and metabolic score. Simple snoring was significantly associated with increased odds for MetS among all participants (OR=2.328, 95% CI: 1.340–4.045) and female participants (OR=2.382, 95% CI: 1.136–4.994) after multivariable adjustment. With regard to MetS components, simple snoring was significantly associated with increased odds for hypertension (OR=1.730, 95% CI: 1.130–2.650), abdominal obesity (OR=1.810, 95% CI: 1.063–3.083), and hyper-triglycerides (TG) (OR=1.814, 95% CI: 1.097–2.998) among all participants, with hypertension (OR=3.493, 95% CI: 1.748–6.979) among males and with abdominal obesity (OR=2.306, 95% CI: 1.245–4.270) and hyper-TG (OR=2.803, 95% CI: 1.146–6.856) among females after multivariable adjustment. Conclusions. After excluding the influence of repeated apnea and hypoxia, simple snoring was still significantly associated with MetS, especially in women. Furthermore, the associations were more obvious for hypertension among males and for abdominal obesity and hyper-TG among females. In addition to OSA, simple snoring also should be valued.